The effect of islands of improvement on the maturity models for industry 4.0: the implementation of an inventory management system in a beverage factory - Dantas, Rafaela; Barbalho, Sanderson César Macêdo (Brazilian Journal of Operations & Production Management, 2021)
Goal: Industry 4.0 has the main purpose to turn the company into an agile organization, able to adapt continuously to the dynamicity of the market. Thus, to reach this target, the business should be aware of its current level of readiness and it needs to establish digital strategies to reach higher levels. The goal of this research is to explore how improvements in industry 4.0 can improve companies´ business processes. Design / Methodology / Approach: The present study is action research that initially identified the most suitable maturity model in Industry 4.0 in the scientific and practitioner literature. Furthermore, the chosen model was applied in a beverage manufacturer to evaluate its current maturity level. Some Industry 4.0 improvements were implemented on the warehouse as part of the company’s digital strategy into which it was integrated the inventory management system with new digital solutions. Finally, interviews were conducted and data was gathered from companies indicators. Results: The conduct of the action research revealed the current status of the company and how storage management contributed to its digital transformation process. A phenomenon of islands of improvement is discussed at the end. Limitations of the investigation: Our main limitation is our case study approach. Additionally, more interviews crossing functional areas could bring further elements about the perception of improvements that each functional group had at the end of the implementation process. Practical implications: The case study suggests that applications of maturity models can generate the phenomena of islands of improvements. Managers must take this situation into account to plan digital transformation in the whole company. Originality / Value: The phenomena of the island of improvement is suggested to be a side effect of implementing industry 4.0 based on maturity models. Keywords: Industry 4.0; maturity model; logistics; inventory; storage management systems; RFID.